EXTENT AND MAGNITUDE OF CATECHOLAMINE SURGE IN PEDIATRIC BURNED PATIENTS - Kulp, Gabriela A (2010)
Increased catecholamine (CA) levels after severe burn are associated with stress, inflammation, hypermetabolism and impaired immune function. The CA secretion profiles in burned patients are not well described. Mechanisms, duration and extent of CA surge are unknown. The purpose of this large unicenter study was to evaluate the extent and magnitude of CA surge following severe burn in pediatric patients. Patients admitted between 1996 and 2008 were enrolled in this study. Twenty-four-hour urine collections were performed during acute hospitalization and up to 2 years post burn. Results from the samples collected from 12 normal, healthy volunteers were compared with the data from the burned patients. Relevant demographic and clinical information was obtained from Medical Records. Student’s t-test and one way ANOVA were used to analyze the data where appropriate. Significance was accepted at p<0.05. Four-hundred thirteen patients were enrolled in this study, 17 patients died during acute hospitalization. Burn caused a marked stress and inflammatory response, indicated by massive tachycardia and elevated pro-inflammatory cytokines. In burned patients, CA levels are consistently and significantly modulated after burn when compared to the levels in normal, healthy volunteers. CA levels were significantly higher in males compared to females, correlated with burn size in burns over 40% and were increased in older children. There were differences over time in survivors vs. non-survivors, with CA levels significantly higher in non-survivors at 2 time points. Inflammatory cytokines show a similar profile during the study period. Our study gives clinicians a useful insight into the extent and magnitude of CA elevation to better design treatment strategies.